# math

posted by Andrea

1. Steve

√(-6)/(√(-3) √(-4))
= (√6 i)/(√3 i * √4 i)
= (√6 i)/(2√3 i^2)
= (√3*√2 i)/(-2√3)
= -√2 i/2
= 0 - 1/√2 i

## Similar Questions

1. ### ml

Evaluate the expression 25/23 and write your answer as a fraction in simplest form.
2. ### math

is zero a multiple of every number? Find the prime factorization of the number, and write it in exponent form. 198 Compute the value of the given expression. _|8|_ |11-8| Evaluate the expression. -8x + 8y, for x = 8 and y = -1
3. ### algebra

^ = exponent **show work please A sheet of 67-pound paper has a thickness of 100^-1 inch. a. write and evaluate an expression for the total thickness of 5 sheets of 67-pound paper b. write and evaluate an expression for the total thickness …
4. ### Math

Evaluate the expression for t • 1/8 for the given value of t. Write the answer in the simplest form. t = 4/9
5. ### Algebra

Use a calculator to evaluate the expression. Write the result in scientific notation and in decimal form. Did I do think correctly?
6. ### math

the expression 10x^2+6x^3 is the result of applying the distributive property to the expression 2x^2(5+3x). write the expression such that you applied the distributive to your expression it will give the result presented 1) m^2(a+b)+m^3(a+b) …
7. ### Math

Write an algebraic expression for each word phrase on the board. Evaluate each expression for x=2 3 times x=6 Expression: 3x